2021
DOI: 10.1080/00325899.2021.1943920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different WC particle shapes on laser-exposed microstructures during the directed energy deposition

Abstract: Tungsten carbide (WC) in Ni-based powders is a promising candidate for laser-based additive manufacturing because WC is an extremely hard material, whereas Ni is tough and weldable. However, WC particles that are directly exposed to a laser beam can be degraded or disintegrated into tungsten and carbon as a result of excess energy. In contrast, particles in the melt pool are relatively stable. In this study, the direct energy deposition method was used with irregular and spherical WC particles in metal powder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It can be used as reinforcement in iron, cobalt, nickel, and titanium-based alloys. 13 One of the materials, which can be produced with the LAM technique, is steel parts. According to the literature, 14 the materials manufactured by LAM have weak mechanical properties like wear resistance and tensile strength.…”
Section: Wc Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be used as reinforcement in iron, cobalt, nickel, and titanium-based alloys. 13 One of the materials, which can be produced with the LAM technique, is steel parts. According to the literature, 14 the materials manufactured by LAM have weak mechanical properties like wear resistance and tensile strength.…”
Section: Wc Compositesmentioning
confidence: 99%
“…It was found that the ƞ phase and unmelted WC/W 2 C powders were transformed to M 2 C by reheating regions. Lee et al 13 assessed the effect of various WC particle shapes on the microstructures of WC/Ni composites fabricated by the DED method. They concluded that the irregular WC particles were more affected by lasers than spherical particles under a similar LAM process.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…With that said, a variety of AM processes have demonstrated the ability to fabricate cemented carbides and other ceramic‐based materials like oxides, 17–20 nitrides, 21 and carbides 22 . For example, the directed energy deposition process can fabricate large grain WC cemented carbides onto a steel substrate 23,24 . Konyashin et al.…”
Section: Introductionmentioning
confidence: 99%
“…22 For example, the directed energy deposition process can fabricate large grain WC cemented carbides onto a steel substrate. 23,24 Konyashin et al printed WC-Co specimens using the electron beam process. 25 Several publications utilized the laser powder bed fusion (LPBF) process to print with WC-Co, [26][27][28][29] WC-Fe, [30][31][32] and WC-Ni.…”
Section: Introductionmentioning
confidence: 99%